(untitled) - Matthews, Bernard E. (Cambridge, U.K.,New York, NY, USA, 1998)
This introductory undergraduate textbook provides a concise, clear and affordable overview of parasite biology for students and non-specialists, to equip them for approaching more technical and detailed literature. Using examples from all groups of animal parasites, the text considers the various stages of a parasite's life cycle from finding hosts to surviving within the host. The significance of damage caused by parasites and approaches to control are discussed, giving the book a well-rounded approach for those new to the subject or revising key points. A key feature of the book is its comparative rather than systematic approach. Suitable for all introductory parasite courses in biology, zoology and human and veterinary medicine.
Keywords: Parasitology,Ký sinh trùng học